ANALISIS HUKUM TERHADAP PENGGELEDAHAN TANPA IZIN MENURUT KITAB UNDANG-UNDANG HUKUM ACARA PIDANA (KUHAP) - Liza Deshaini; Muhammad Nur Amin; Sudarna (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
Juridical Review Unauthorized Search Based on Article 34 Paragraph (1) of the Criminal Procedure Code (KUHAP), is as follows:bIn very necessary and urgent circumstances the investigator can carry out search without first obtaining permission from the Chief Justice Local country. With the obligation to immediately report this to the Chairman local court for approval. And the search procedure in an urgent situation is that a search can be carried out immediately without prior permission from the Head of the District Court for the places being searched, within two (2) days after the search the investigator makes an official report containing the course and results of the search, the investigator's obligation to immediately report to the Chief Justice of the District Court.